Peningkatan Kapasitas Kader Posyandu dalam Home Care pada Ibu Hamil dengan Anemia - Nuryanti, Yayuk; Mansa, Gidion; Pratiwi, Nunuk (Universitas Muhammadiyah Yogyakarta, 2024)
Pregnant women prone to have anemia if the Hb level is less than 11.0 g/dL. This condition poses a high risk of health problems, so detection of anemia in pregnant women must be done as early as possible. Posyandu cadres can carry out this task as long-term health workers. If you find signs of anemia, you can immediately take them to a health facility for further examination. The aim of this service is to increase the knowledge of posyandu cadres about how to physically examine signs of anemia and apply home care to pregnant women. The activity was carried out in two stages. The first stage was training for 10 Posyandu cadres, and the second stage was practice. Posyandu cadres carried out physical examinations for signs of anemia in pregnant women. Next, health workers checked hemoglobin (Hb) levels. Pregnant women who are diagnosed with anemia with Hb less than 11 g/dL, were then given home care by local cadres. Of the 18 pregnant women, 8 were detected as having anemia. Next, the cadres carried out home care by providing boiled sweet potato leaves for one week. The results of the activity showed that cadres’ knowledge increased as seen from an increase in the average score of 12 points from the pre-test compared to the post-test. Qualitatively, the cadres expressed their happiness at being able to treat pregnant women with anemia by using local ingredients. This activity can be carried out with other pregnant women as an effort to improve the health status of mothers and children.